UNVEILING STUDENT PERSPECTIVES: EXPLORING THE IMPACT OF GAMIFICATION IN ENGLISH LANGUAGE TEACHING - Yazid, S Rizal; Heriyawati, Dwi Fita; Mistar, Junaidi (University of Kuningan, 2024)
This study examines the impact of gamification on English language teaching, focusing on student engagement, motivation, and overall learning experiences. To address a research gap in understanding the specific effects of gamified learning environments in this context, this qualitative research adopts a case study design, employing semi-structured interviews with ten students attending Islamic Senior High Schools. Thematic analysis reveals three main themes: Positive Impact on Engagement and Attitude, Motivation Through Competition, and Effective and Enjoyable Learning Activities. Participants have observed increased class attendance, a boost in their enthusiasm, and positive attitudes toward learning English, attributing these changes to gamification. The findings indicate that gamification not only positively has a beneficial impact on both student engagement and motivation but also enhances the overall learning environment. Implications for educators and policymakers involve the potential integration of gamified strategies to create dynamic, attractive language learning environments. The study provides new insights into the existing body of knowledge on the use of gamification in education, emphasizing the need for future investigation into its long-term effects on language competency and cultural contexts.